EP1322 Identification of upper and lower lymphatic pathways during mapping of sentinel pelvic lymph nodes in a patient with endometrial cancer. (1st November 2019) - Biliatis, I; Mitsopoulos, V
Abstract : Introduction/Background: It is well known that the lymphatic drainage of the uterus is mainly performed through 2 distinct pathways. The first is called upper pathway and drains the lymph from the parametrium and through the external iliac artery, while the second is called lower pathway and uses a system through the internal iliac artery. These 2 pathways most of the times are not connected. The lower pathway usually drains at the presacral lympatic basin. Methodology: With ICG injection at the cervix and using the Xi Robotic system we managed to clearly identify these 2 distinctive pathways Results: We believe that this is important as identifying a pre-sacral lymph node through the identification of the lower lymphatic pathway could potentially improve the sensitivity of the sentinel node technique in patients with endometrial cancer Conclusion: Identification of both lymphatic pathways using ICG and Robotic technology is feasible and might improve the sensitivity and detection rate of sentinel node in endometrial cancer patients Disclosure: Nothing to disclose